Solar spectral measurements and modeling - Bird, Richard E.; Hulstrom, Roland L. (Solar Energy Research Institute, 1981)
A newly developed spectroradiometer for routine measurement of the solar spectra is described. This instrument measures the solar spectrum between 300 and 2500 nm in less than 2.5 min, with 0.7-nm resolution in the visible and 10-nm resolution in the infrared. Many examples of global, direct, and diffuse spectra are illustrated for Bedford, Mass. and Golden, Colo. The effects of air mass, turbidity, and sun tracking on the spectrum are presented, and radiative transfer modeling capabilities and comparisons between models and between models and experiment are discussed.